Miróbriga: study of roman mortars - Hao, Alvin Chua Sern (2019)
Mirobriga is a Roman site located in the municipality of Santiago do Cacém, in Setúbal, a district in the southwest of Portugal. This settlement is mentioned in the ancient literature, and the archaeological evidence suggests that the city was developed by the Romans as an urban centre around the 1st century AD. For this study, 17 mortar samples were collected from various buildings – the Western Thermae, Domus 3, Domus 4, Taberna 1, Taberna 2, the ‘Hospedaria’, the macellum, and the forum. The chemical, mineralogical, and microstructural characterisation of the samples was performed using a number of complementary techniques – stereomicroscopy, polarised light microscopy, chemical and granulometric analysis, thermogravimetric analysis (TGA), powder X-ray diffraction (XRD), and variable pressure scanning electron microscopy-energy dispersive spectrometry (SEM-EDS). The results show that the aggregates consist mainly of quartz, whereas the binder was lime-based. The sand for the aggregates was sourced locally (within a 20 km radius), whilst the limestone for the binder may have been obtained from local quarries (within a 20 km radius), or imported from further afield (possibly from São Brissos). Most of the samples have a binder to aggregate ratio of 1 : 3, and display some degree of hydraulicity. From the results, it may be said that most of the samples are similar, indicating the contemporaneity of the buildings. Nevertheless, several samples (MRBT-1E, MRBT-2E, MRBH7-12E, MRBH7-13BE, MRBH7- 13VE, and MRBF-16E) are different, which may be attributed to their function. Keywords: Mirobriga, Roman mortars, stereomicroscopy, polarised light microscopy, SEM-EDS, TGA, XRD, raw materials, provenance; Resumo: O sítio arqueológico de Mirobriga localiza-se junto à cidade de Santigo do Cacém (distrito de Setúbal) no sudoeste de Portugal. Este sítio é mencionado na literatura antiga e as evidências arqueológicas sugerem que a cidade foi desenvolvida pelos romanos, como um centro urbano, por volta do século I dC. Para este estudo, foram recolhidas 17 amostras de argamassa de vários edifícios, nomeadamente, Termas Ocidentais, Domus 3 e 4, Taberna 1 e 2, a Hospedaria, macellum e fórum. A caracterização química, mineralógica e microestrutural das amostras foi realizada por recurso a técnicas complementares – estereomicroscopia, microscopia de luz polarizada, análise química e granulométrica, análise termogravimétrica (ATG), difração de raios-X (DRX), microscopia eletrónica de varrimento com espectroscopia de raios X por dispersão de energias (MEV-EDS). Os resultados mostram que a maioria das amostras são similares, nomeadamente, no que respeita ao tipo de agregados, com predomínio de quartzo e ao tipo de ligante, cal calcítica. A areia para os agregados era de proveniência local (num raio de 20 km) enquanto que o calcário para o ligante pode ter sido obtido em pedreiras locais (num raio de 20 km) ou transportado de mais longe (provavelmente de São Brissos). A maioria das amostras apresenta uma razão ligante agregado de 1:3 e um grau de hidraulicidade análogo., indicando a contemporaneidade dos diferentes edifícios estudados. As diferenças observadas em algumas amostras (MRBT-1E, MRBT-2E, MRBH7-12E, MRBH7-13BE, MRBH7-13VE, and MRBF-16E) podem ser atribuídas à função desempenhada pelas mesmas.